Soft skills in action: developing tourism students skills through interdisciplinarity - Vasconcelos, Sandra (2022)
Tourism research has highlighted the strategic need to identify and assess relevant skills for the sector to ensure organizations’ competitiveness. Describing an interdisciplinary project carried out at the School of Hospitality and Tourism (Polytechnic Institute of Porto), this paper aims to contribute to the ongoing debate on the importance of soft skills in the tourism industry and the role played by higher education institutions and tourism education in promoting their development. Working toward bridging the gap between academia and the labor market, this project covered five different courses and challenged students to write research papers, drawing from interviews with stakeholders from different tourism subsectors. Making use of a collaborative approach, based on complementarity and field work, the project succeeded, exceeding initial expectations and enhancing participants’ teaching and learning experiences. In addition to being aligned with current trends in tourism education, it also provides valuable insights on the affordances and attainability of interdisciplinarity, ultimately informing further joint initiatives within this scope.